Plant lectins and their potential in controlling phytophagous insects - Ngoc Quynh, Le Thi; Ha, Chu Duc; Ket, Nguyen Van; Dung, Le Tien (Academia Journal of Biology, 2015)
Phytophagous insects is one of the major biological constraints in crop production. To cope with continuous threat from insects, plants produce insecticidal peptides or proteins. Plant lectins are carbohydrate binding proteins, one of the most important secondary metabolites which also serve as a defense tool against plant-eating organisms. Although most lectins have moderate effects to development, fecundity or growth of insect, several lectins are highly toxic to insects. In the last decade, many studies reported a role of lectins in pest management. In particular, several plant lectins respond to different kinds of stress such as drought, fire, wounding, high-salinity, hormone treatment and pathogen attack. This group of lectin is called as “inducible plants lectin”. This review summarized recent progresses in research on the application of lectin as a potential approach for integrated pest management.